A Comparative Analysis of Indonesia and Turkey’s Foreign Policy Toward The Middle East: A Case of Palestine Issue - Noor Fahmi Pramuji (Universitas Bosowa, 2020)
This paper aims to perform a comparative analysis of Turkey and Indonesia's foreign policy on Palestine Issue. It applies neoclassical realism as one of foreign policy theory. It discusses changing dynamics and influential factors shaping Turkey and Indonesia’s Palestine policies at the unit and systemic level of analysis. It summarises that the factors of leaders' perceptions upon international systemic changing trends and pressures, state power have become influential factors. During AK Party's eras in Turkey, its domestic politics has undergone domestic transformations namely public opinion and civil society's roles that influence to the foreign policy, the emergence of civilian leader as a new actor of foreign policy, leader factors, an increase of Islamist factor, the Israel-Palestine conflict perceived as the heart of regional instability resulted in Proactive Foreign policy including in the settlement of Palestine issue. Meanwhile, after reform eras in Indonesia, anti-colonialism spirit of 1945 Constitution has been continued as the historical background of Indonesia's engagement. Besides, an increase of Islamist factor in domestic politics namely Islamist-oriented aspirations in domestic public opinion, muslim groups as a moral force, an increasingly role of Islamist parties, and new Indonesia's international orientation and identity at SBY's tenure have affected a continuity of non-recognition policy towards Israel and supporting Palestine in accordance with two-state solution. As well as Indonesia's democratised foreign policy has been conducted through various diplomatic efforts.